Avaliação da técnica de termografia infravermelha para identificação de estruturas ocultas e diagnóstico de anomalias em edificações: ênfase em edificações do patrimônio histórico - Eduardo Cabaleiro Cortizo (2007)
The main objective of this work is to research and evaluate the results of the application of heat transfer techniques: radiation (infrared thermograph) and conduction (thermopar sensors) as a tool of diagnosis of the presence of hidden structures and anomalies at edifications which belong to the Brazilian Historical Patrimony. The utilization of a non-destructive method, mainly infrared thermograph, is highly diffused at European Countries, due to their great historical estate. Nevertheless, Brazils singularity, considering: his tropical position (different climate regime) and both the materials employed in the edifications of the past century and the building techniques, justifies and imposes the assimilation of this technology so as to guarantee and safeguard ourworthy Historical Patrimony. The work proposed was the analysis of an edification historic: São Sebastião das Águas Claras Chapel, built in the XVIIth century using sundried brick, and placed at São Sebastião das Águas Claras district, at Nova Lima, Minas Gerais. Two techniques of evaluation and identification were employed, in spite of the fact that the parameter was the same: temperature. Those techniques distinguishthemselves by the mechanism of observation of the heat transfer phenomena. The results, it was possible to identify hidden wooden and sealing structures (sun-dried brick blocks) at the Chapels wall, and, moreover, the presence of some anomalies. These results are completely validated by the historic documentation of the interventionswhich took place at the Chapel over the years. The evaluation method of edifications, using digital thermograph resources, may enable specialists to take any decisions necessary to conservation and preservation. The singularity and relevance of the present work are unquestionably and urgent on account of the major importance of historical of Brazilian Historical Patrimony. Foreseeing its future, it is possible to guarantee that the use of thermograph will be a fundamental technological tool of diagnosis, assisting the process of taking decisions about proceedings and conservation techniques, restoration and preservation, to be used in historical edifications. Therein, this work offers a perspective and a critical vision to the implementation and advance of this research field.